Eight Five Year Plan (1990-95) and Annual Plan 1991-92 Vol. III Government of Uttar Pradesh - Planning Commission (Planning Commission, 1990)
Summary Statement of Major-head wise Outlays and Expenditure during Seventh Five Year Plan Summary Statement of Major-head wise Outlays during Eighth Five Year Plan Sub-Major-head wise Outlays and Expenditure Physical Targets and Achievements Minimum Needs Programme-Outlays and Expenditure Minimum Needs Programme-Physical Targets Externally Aided Projects-Outlays and Expenditure Externally Aided Projects-Physical Targets and Achievement Centrally Sponsored Schemes-Summary Statement of Outlays & Expenditure Centrally Sponsored Schemes-Outlays and Expenditure Employment in the Seventh Plan/Eighth Plan with the corresponding figures of expenditure/outlay.
Government of Uttar Pradesh, Planning Department